Political Social Responsibility of Council Members in Implementing Public Policy: Case Study of Regional Parliamentarians of Purwodadi Regency in 2020 - Nastain, M.; Nurdiarti, Rosalia Prismarini (Universitas Ahmad Dahlan, 2022)
This article aims to determine council members' involvement in carrying out their duties and responsibilities related to community empowerment. Furthermore, to find out how council members maximize the potential of the region and its community with a power and policy approach. Political CSR is an inherent obligation of parliamentarians because the people elect them in a formal and legal contest. The carried-out mandate should present full responsibility to struggle for the community's welfare in internal work as a legislative product holder and external work in serving the community. This research uses an intrinsic case study approach with the object of research on legislative members in the Grobogan Regency. The socio-political responsibilities of the parliamentarians will be studied based on the triple C approach; they are Community Relations, Community Empowerment, and Community Service. Community relations aim to foster a harmonious relationship between organizations (politicians) and the community to increase social awareness and mutual understanding. Community Empowerment is an effort to develop community potential and overcome existing societal problems. The involvement of council members in community empowerment is implemented in three stages: good community relations, community empowerment in the form of community advocacy, and creating an institution that educates the community and community service by prioritizing comprehensive services.